1986
DOI: 10.1111/j.1365-2923.1986.tb01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Does clinical clerkship alter students' attitudes to a career choice of psychiatry?

Abstract: A 50-item questionnaire, designed to link attitudes to psychiatry directly with how these might influence a career choice of psychiatry, was administered to medical students before and after their clinical clerkship in psychiatry. Many of these changed in a positive direction, e.g. 'job satisfaction', 'life-style', 'training available' and 'multidisciplinary approach'. The influence of important people in their lives was predominantly negative; this may emphasize the impact of psychiatric 'role models'. Male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
2
17
2
2
Order By: Relevance
“…The role of the clinical posting or clerkship in psychiatry in changing attitudes of medical students towards the specialty has also been looked into. Although some studies (Burra et al, 1982;Shelley & Webb, 1986) have suggested that the clinical posting makes the attitude more positive, other studies (Galletly et al, 1995) have found little or no change as a result. A related study (Maidment et al, 2003) involving sixth-form students showed a surprising level of interest in psychiatry, with 12.4% wanting to pursue careers as psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the clinical posting or clerkship in psychiatry in changing attitudes of medical students towards the specialty has also been looked into. Although some studies (Burra et al, 1982;Shelley & Webb, 1986) have suggested that the clinical posting makes the attitude more positive, other studies (Galletly et al, 1995) have found little or no change as a result. A related study (Maidment et al, 2003) involving sixth-form students showed a surprising level of interest in psychiatry, with 12.4% wanting to pursue careers as psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…Budd et al [8] identified that UK medical students who had undertaken clinical psychiatry placements were more positively inclined toward psychiatry following the experience, and positive placement experiences have been shown to improve students' attitudes to psychiatry [16]. Shelly and Webb [17] also reported that psychiatry was ranked higher in career choice following completion of a psychiatry clerkship. Authors identified a positive impact on attitude toward psychiatry following clinical experience including views on job satisfaction, lifestyle, training, and multidisciplinary approaches to psychiatry.…”
mentioning
confidence: 96%
“…Several studies have investigated changes in attitudes of students towards psychiatry and/or to a possible psychiatric career following psychiatric clinical attachments, and none has found that attitudes became more negative. Two found no significant change (Galletly et al, 1995;Calvert et al, 1999), whereas more studies found that attitudes became increasingly positive (Shelley & Webb, 1986;Sivakumar et al, 1986;Creed & Goldberg, 1987;Alexander & Eagles, 1990;Singh et al, 1998;McParland et al, 2003). Studies investigating specific aspects of clinical attachments which might give rise to attitudinal changes have been less common.…”
Section: Undergraduate Influences On Career Choicementioning
confidence: 99%